Implementation Model of Timeliness of BPJS Claims Based on Penomenology Study - Tengku Nilasari; Wahyuni Dian Purwati; Rian Adi Pamungkas (Jurnal Health Sains, 2023)
The purpose of this study was to explore the factors of delay in BPJS claims for inpatients at the Yukum Medical Center Hospital. The type of research in this study using qualitative research using a qualitative approach is expected to produce a basic model in providing the most appropriate recommendations in solving the problem of the timeliness of submitting BPJS claims at the Yukum Medical Center hospital. This subject is the accuracy of BPJS claims. The object of this research is the Yukum Medical Center casemix team. The results of the analysis conclude that the claim procedure already has an SPO/regulation that regulates the procedure for submitting a BPJS claim but has not run according to the SPO/regulation. The delay in BPJS claims in 2021 is around 80%. delays in BPJS claims as a result of the lack of quality of the casemix team's human resources and inaccurate and incomplete medical resumes. Factors causing delays in BPJS claims from aspects of Man, Method, Machine, Material, and Money. Expected recommendations so that recommendations/solutions are proposed again. The claim procedure is in accordance with the implementation flow, but the SPO/regulation has not been running well. BPJS RS claim. Yukum Medical Center 80% of 2021 claims are late. Factors causing delays in BPJS claims there is no evaluation of the competency of the casemix team (man), late and incomplete medical resumes (material), lack of printers when there is an increase in the number of patients (mechine), lack of budget for HR training (money). The BPJS claim recommendations at the Yukum Medical Center Hospital have been running but the results of the implementation have not been in line with expectations, so recommendations are needed.